2018
DOI: 10.1016/j.jvs.2018.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular injuries found in acute type B aortic dissections are associated with blood pressure derangements and poor outcome

Abstract: In our series, CVI in ATBAD is more frequent than previously reported and is associated with increased mortality. The most common causes are related to cerebral hypoperfusion. Higher MAP on presentation and greater decline in MAP are associated risk factors for hypoperfusion-related CVI. A less aggressive approach to lowering MAP in ATBAD warrants further study in an attempt to reduce CVI in ATBAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Reference lists for articles selected for inclusion in the study were also searched for relevant articles. The full Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) (6) flow diagram outlining the study selection process is available in Figure S1.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…Reference lists for articles selected for inclusion in the study were also searched for relevant articles. The full Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) (6) flow diagram outlining the study selection process is available in Figure S1.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…Presently, the antihypertensive therapy of AD is controversial in that the current clinical guidelines of BP control lack highlevel clinical evidence (7)(8)(9)(10), and clinical data have indicated no significant improvement in the efficacy of antihypertensive therapy for AD over the last two decades (1). Several studies found that the target BP level of 100-120 mm Hg was not suitable for all AD patients because rapid intensive BP lowering may lead to organ ischemia for patients with high basal BP (11,34,35). Therefore, individualized antihypertensive therapy for AD patients is essential.…”
Section: The Review In the Context Of Other Literaturementioning
confidence: 99%
“…Blood pressure (BP) control is a critical approach to reduce the complication in the perioperative treatment of acute Type B aortic dissection [1]. The rise of blood pressure or its fluctuation is related to multiple factors, including pain, constipation, anxiety, and insomnia.…”
Section: Introductionmentioning
confidence: 99%